Influence of fibre aspect ratio on rheological performance for 3D printable materials - Angellee, Raymond Rafael (2019)
The concept of 3D printed materials has been widely used in the industries of present era. In particular, the construction sector is not unfamiliar with the term 3D printed concrete (3DPC). Improvements on the pumpability of concrete mix during printing have been continuously researched. However, fibre, a material widely researched in the mixture of common concrete mix, has not yet to be discussed upon regarding its influence towards 3D printed concrete.